Electrochemical preparation and properties of a Mg–Li–Y alloy via co-reduction of Mg(ii) and Y(iii) in chloride melts. Issue 23 (13th April 2021) - Wang, Guan-Zhong; Liu, Yao; Ji, De-Bin; Zhu, Ling-Yue; Ji, De-Qiang; Yuan, Dan-dan; Zhang, Mi-Lin; Wu, Hong-Jun
Abstract : Mg–Li based alloys have been widely used in various fields. Abstract : Mg–Li based alloys have been widely used in various fields. However, the widespread use of Mg–Li based alloys were restricted by their poor properties. The addition of rare earth element in Mg–Li can significantly improve the properties of alloys. In the present work, different electrochemical methods were used to investigate the electrochemical behavior of Y(iii ) on the W electrode in LiCl–KCl melts and LiCl–KCl–MgCl2 melts. In LiCl–KCl melts, typical cyclic voltammetry was used to study the electrochemical mechanism and thermodynamic parameters for the reduction of Y(iii ) to metallic Y. In LiCl–KCl–MgCl2 melts, the formation mechanism of Mg–Y intermetallic compounds was investigated, and the results showed that only one kind of Mg–Y intermetallic compound was formed under our experimental conditions. Mg–Li–Y alloys were prepared via galvanostatic electrolysis, and XRD and SEM equipped with EDS analysis were used to analyze the samples. Because of the restrictions of EDS analysis, ICP-AES was used to analyze the Li content in Mg–Li–Y alloys. The microhardness and Young's modulus of the Mg–Li–Y alloys were then evaluated.